1999
DOI: 10.1111/j.1651-2227.1999.tb01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding patterns in exclusively breastfed infants: a longitudinal prospective study in Uppsala, Sweden

Abstract: Hörnell A, Aarts C, Kylberg E, Hofvander Y, Gebre-Medhin M. Breastfeeding patterns in exclusively breastfed infants: a longitudinal prospective study in Uppsala, Sweden. Acta Paediatr 1999; 88: 203-11. Stockholm. ISSN 0803-5253 Exclusive breastfeeding was studied among 506 infants in Uppsala, Sweden, based on daily recordings during the first 6 mo. The mothers had previously breastfed at least one infant for at least 4 mo. Most of the mothers considered that they breastfed on demand. Wide variations in bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 22 publications
(31 reference statements)
10
36
2
1
Order By: Relevance
“…The other research aims focus on the universality of the association between maternal education EBF, something that has received much attention in previous studies (Colodro-Conde et al 2011), leading it to be incorporated as a control variable in a wide array of other studies. There is a universal assumption that a higher maternal education leads to higher breastfeeding rates in developed nations (Hörnell et al 1999;Bertini et al 2003;Colodro-Conde et al 2011). Our design allowed us to test whether this association is positive across all population groups in Belgium, which was our second research aim, or if the educational benefits are stronger for some groups compared to others, which was our third research aim.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other research aims focus on the universality of the association between maternal education EBF, something that has received much attention in previous studies (Colodro-Conde et al 2011), leading it to be incorporated as a control variable in a wide array of other studies. There is a universal assumption that a higher maternal education leads to higher breastfeeding rates in developed nations (Hörnell et al 1999;Bertini et al 2003;Colodro-Conde et al 2011). Our design allowed us to test whether this association is positive across all population groups in Belgium, which was our second research aim, or if the educational benefits are stronger for some groups compared to others, which was our third research aim.…”
Section: Discussionmentioning
confidence: 99%
“…Women's access to education has long been recognized as a fundamental right and a central policy aim of many international communities and countries (Kabeer 2005). In this study, education is especially relevant: empirical research has shown its well-established role in infant feeding decisions (Hörnell et al 1999;Bertini et al 2003;Colodro-Conde et al 2011;Raffle et al 2011); it is considered as a more fixed indicator of the mothers socio-economic status (Kwok & Yankaskas 2001;Heck et al 2006), and there is a demonstrated close link between education and gender equality (Malhotra et al 2003). This connection is most visible on issues of maternal health (Malhotra et al 2003), where education is positively associated with higher use of maternal care services and improved health outcomes.…”
Section: Maternal Education As An Individual Pathway To Exclusive Brementioning
confidence: 98%
See 1 more Smart Citation
“…Research suggested that complementary foods offered to infants before 6 months of age tend to displace breastmilk without conferring any growth advantage over exclusive breastfeeding [44]. Early introduction of other foods or drinks is an area of concern mainly because it marks the end of exclusive breastfeeding which has protective effects [45]. …”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies show that not only do babies show a three-fold variation in the amount they take per day, they also show a wide variation in their patterns of milk intake. 33,50 During a meal or a breastfeeding session, the baby may feed from one breast only (an unpaired breastfeed), feed from both breasts within 30 minutes (two paired breastfeeds), or the baby may have a cluster of breastfeeds (feeding again from the first breast within 30 minutes of feeding on the second). In a recent study of exclusively breastfeeding babies between 1 and 6 months old in Western Australia, 33 13% of babies always took paired breastfeeds, 30% of babies always took unpaired breastfeeds, and most babies had paired and unpaired breastfeeds.…”
Section: Breastfeeding Patternsmentioning
confidence: 99%